Effect of Neonatal Treatment With the NMDA Receptor Antagonist, MK-801, During Different Temporal Windows of Postnatal Period in Adult Prefrontal Cortical and Hippocampal Function - Plataki, Maria E.; Diskos, Konstantinos; Sougklakos, Christos; Velissariou, Marouso; Georgilis, Alexandros; Stavroulaki, Vasiliki; Sidiropoulou, Kyriaki (Frontiers in Behavioral Neuroscience, 2021)
The neonatal MK-801 model of schizophrenia has been developed based on the neurodevelopmental and NMDA receptor hypofunction hypotheses of schizophrenia. This animal model is generated with the use of the NMDA receptor antagonist, MK-801, during different temporal windows of postnatal life of rodents leading to behavioral defects in adulthood. However, no studies have examined the role of specific postnatal time periods in the neonatal MK-801 (nMK-801) rodent model and the resulting behavioral and neurobiological effects. Thus, the goal of this study is to systematically investigate the role of NMDA hypofunction, during specific temporal windows in postnatal life on different cognitive and social behavioral paradigms, as well as various neurobiological effects during adulthood. Both female and male mice were injected intraperitoneally (i.p.) with MK-801 during postnatal days 7–14 (p7–14) or 11–15 (p11–15). Control mice were injected with saline during the respective time period. In adulthood, mice were tested in various cognitive and social behavioral tasks. Mice nMK-801-treated on p7–14 show impaired performance in the novel object, object-to-place, and temporal order object recognition (TOR) tasks, the sociability test, and contextual fear extinction. Mice nMK-801-treated on p11–15 only affects performance in the TOR task, the social memory test, and contextual fear extinction. No differences were identified in the expression of NMDA receptor subunits, the synapsin or PSD-95 proteins, either in the prefrontal cortex (PFC) or the hippocampus (HPC), brain regions significantly affected in schizophrenia. The number of parvalbumin (PV)-expressing cells is significantly reduced in the PFC, but not in the HPC, of nMK-801-treated mice on p7–14 compared to their controls. No differences in PV-expressing cells (PFC or HPC) were identified in nMK-801-treated mice on p11–15. We further examined PFC function by recording spontaneous activity in a solution that allows up state generation. We find that the frequency of up states is significantly reduced in both nMK-801-treated mice on p7–14 and p11–15 compared to saline-treated mice. Furthermore, we find adaptations in the gamma and high gamma activity in nMK-801-treated mice. In conclusion, our results show that MK-801 treatment during specific postnatal temporal windows has differential effects on cognitive and social behaviors, as well as on underlying neurobiological substrates.